Antitumor Platelet‐Mimicking Magnetic Nanoparticles - Rao, Lang; Bu, Lin‐Lin; Meng, Qian‐Fang; Cai, Bo; Deng, Wei‐Wei; Li, Andrew; Li, Kaiyang; Guo, Shi‐Shang; Zhang, Wen‐Feng; Liu, Wei; Sun, Zhi‐Jun; Zhao, Xing‐Zhong (Advanced functional materials, 2017)
Nanoparticles possess the potential to revolutionize cancer diagnosis and therapy. The ideal theranostic nanoplatform should own long system circulation and active cancer targeting. Additionally, it should be nontoxic and invisible to the immune system. Here, the authors fabricate an all‐in‐one nanoplatform possessed with these properties for personalized cancer theranostics. Platelet‐derived vesicles (PLT‐vesicles) along with their membrane proteins are collected from mice blood and then coated onto Fe3O4 magnetic nanoparticles (MNs). The resulting core–shell PLT‐MNs, which inherit the long circulation and cancer targeting capabilities from the PLT membrane shell and the magnetic and optical absorption properties from the MN core, are finally injected back into the donor mice for enhanced tumor magnetic resonance imaging (MRI) and photothermal therapy (PTT). Meanwhile, it is found that the PTT treatment impels PLT‐MNs targeting to the PTT sites (i.e., tumor sites), and exactly, in turn, the enhanced targeting of PLT‐MNs to tumor sites can improve the PTT effects. In addition, since the PLT membrane coating is obtained from the mice and finally injected into the same mice, PLT‐MNs exhibit stellar immune compatibility. The work presented here provides a new angle on the design of biomimetic nanoparticles for personalized diagnosis and therapy of various diseases. Platelet (PLT) membranes are collected from mice blood and further used to coat magnetic nanoparticles (MNs). And the resulting platelet‐mimicking particles (PLT‐MNs) are then injected back into the donor mice for enhanced tumor magnetic resonance imaging and photothermal therapy. This work presents a new angle on the design of advanced functional materials for personalized cancer theranostics.